Optimizing pediatric AKI diagnosis: a patient-tailored meta-analysis of urinary TIMP-2/IGFBP7 performance across clinical scenarios and assay platforms - Huang, Yilong; Liu, Yunguang; Lin, Na; Qi, Guangzi; Shao, Wen (Frontiers in Pediatrics, 2025)
ObjectiveTo systematically evaluate the diagnostic value of urinary cell cycle arrest biomarkers, tissue inhibitor of metalloproteinases-2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP7), for the early diagnosis of acute kidney injury (AKI) in children using a meta-analysis.MethodsNine databases were searched (inception-May 2025). Two reviewers independently screened studies, extracted data, and assessed quality (QUADAS-2). Bivariate models (STATA 18.0) generated pooled estimates.Results15studies (1,338participants; 337 AKI cases) were included. Overall accuracy: Sensitivity 0.84 (95% CI: 0.71–0.91), Specificity 0.85 (95% CI: 0.76–0.91), AUROC 0.91. Key subgroups: High-risk Neonates: AUROC 0.96, NLR 0.13 (95% CI: 0.02–0.78), Critically Ill/Sepsis: AUROC 0.88, NLR 0.15 (95% CI: 0.04–0.64), ELISA testing: Sensitivity 0.88 (95% CI: 0.70–0.96), NLR 0.15 (95% CI: 0.05–0.43); NephroCheck® Test: AUROC 0.79; Funnel plot asymmetry suggested publication bias.ConclusionsTIMP-2/IGFBP7 show high diagnostic accuracy across pediatric settings, supporting their clinical utility.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251089957, PROSPERO CRD420251089957.